Interaction of the water soluble fraction of MSW-composts with Pb(II) and Cu(II) ions. (1st May 2017) - Castaldi, Paola; Demurtas, Daniela; Silvetti, Margherita; Deiana, Salvatore; Garau, Giovanni
Abstract: In this study we report on the interactions between the water-soluble fraction (WSF) of two municipal solid waste composts (C1- and C2-WSF) with Pb(II) and Cu(II) ions at pH 4.5. The Me(II) addition to the compost-WSFs led to the formation of soluble Me(II)-organic complexes (as highlighted by FT-IR spectroscopy), and to a decrease of the trace metals' solubility, which was greater for Pb(II) than Cu(II). This was due to the formation of insoluble Me(II) complexes involving the water-soluble organic carbon (WSOC) and the inorganic anions within both WSFs [1.10 and 0.62 mmol L −1 and 2.06 and 0.42 mmol L −1 of Pb(II) and Cu(II) precipitated from C1- and C2-WSF respectively, when 6.4 mmol L −1 Me(II) was added]. A loss of WSOC from both WSFs, i.e. ∼13% and <5%, was detected in the systems containing 6.4 mmol L −1 Pb(II) and Cu(II) respectively. A significant contribution in the formation of Pb(II) precipitates was also due to phosphate, chloride and sulphate anions, since their concentrations in the WSF decreased of 80, 25 and 90%, respectively, after the addition of 6.4 mmol L −1 Pb(II). A decrease of phosphate anions in both WSFs (∼30%) was found in the systems containing Cu(II). Highlights: The WSFs of two MSW-composts affected the solubility of Cu(II) and Pb(II) at pH 4.5. Organic and inorganic components of WSFs are involved in the Me(II) precipitation. Me(II)-precipitation induced by compost-WSF was higher for Pb(II) than Cu(II). Phosphate and sulphate anions in WSF affected mainly Pb(II) precipitation. Cu(II) precipitation was largely governed by water soluble humus-like fraction.